Facies Analysis and Depositional Environments of the Ubaid Formation, Western Iraq - Altaee, Noor T.; Malak, Zaid A. (Iraqi Journal of Science, 2021)
The Early Jurassic (Liassic) sequence crops out in numerous anticlines of the high folded zone of north and north-east Iraq and in the Rutba subzone (including Ubaid Formation) in west Iraq. The present study deals with siliciclastic / carbonate rocks of the 58 m-thick Ubaid Formation at Zor Hauran valley in south western Iraq. The formation consists of two parts; the lower part is composed of pebbly coarse sandstone and greenish to yellowish soft marl alternated with marly dolostone, while the upper part is characterized by light brown, well bedded dolostone, with stromatolite structure in some locations. Oval, light to dark brown nodules of chert are also present. A detailed field lithological description and facies analysis of the Ubaid Formation were performed for thin sections. It is composed of five main microfacies; dolomitized mudstone, dolomitized bioclastic wackstone, dolomitized pelloidal packstone, dolomitized oolitic grainstone, and bindstone, in addition to two lithofacies: marl and pebbly sandstone. These facies reflect the deposition from the environment of the lower supratidal to intertidal zone and the encompassing shallow scaffold secured shoal - marine environment with cautious water circulation.